The impact of the International Livestock Research Institute - McIntire, John M.; Grace, Delia (CAB International, 2020)
Providing the first evidence-based global estimates of the many scientific, economic, policy, and capacity development impacts of livestock research in and for developing countries, this volume is an indispensable guide and reference for veterinarians, animal and forage scientists, and anyone working for the equitable and sustainable development of the world's poorer agricultural economies.